ChemInform Abstract: 6, 7‐Seco‐ent‐Kaurane‐Type Diterpenoids from Isodon eriocalyx var. laxiflora. Issue 11 (March 2015) - Wang, Wei‐Guang; Yan, Bing‐Chao; Li, Xiao‐Nian; Du, Xue; Wu, Hai‐Yan; Zhan, Rui; Li, Yan; Pu, Jian‐Xin; Sun, Han‐Dong
Abstract The isolation, structure elucidation and bioevaluation of twenty nine 6, 7‐seco‐ent‐kaurane‐type diterpenoids including 18 new ones, laxiflorolides C‐T [structure examples (I)‐(V)] is described.